Evaluating Impacts of Recent Arctic Sea Ice Loss on the Northern Hemisphere Winter Climate Change. Issue 7 (6th April 2018) - Ogawa, Fumiaki; Keenlyside, Noel; Gao, Yongqi; Koenigk, Torben; Yang, Shuting; Suo, Lingling; Wang, Tao; Gastineau, Guillaume; Nakamura, Tetsu; Cheung, Ho Nam; Omrani, Nour‐Eddine; Ukita, Jinro; et al.
Abstract: Wide disagreement among individual modeling studies has contributed to a debate on the role of recent sea ice loss in the Arctic amplification of global warming and the Siberian wintertime cooling trend. We perform coordinated experiments with six atmospheric general circulation models forced by the observed and climatological daily sea ice concentration and sea surface temperature. The results indicate that the impact of the recent sea ice decline is rather limited to the high‐latitude lower troposphere in winter, and the sea ice changes do not significantly lead to colder winters over Siberia. The observed wintertime Siberian temperature and corresponding circulation trends are reproduced in a small number of ensemble members but not by the multimodel ensemble mean, suggesting that atmospheric internal dynamics could have played a major role in the observed trends. Plain Language Summary: Understanding the mechanism governing the ongoing global warming is a major challenge facing our society and its sustainable growth. Together with the CO2 ‐forced warming, the concurrent polar sea ice loss might also have contributed to the observed Arctic warming amplification and also to the cooling trends over Eurasia through a dynamical teleconnection. However, previous individual modeling studies suggest widely different findings on the role of sea ice loss in Northern Hemisphere climate change. To help resolve this controversy, we used satellite‐derived sea ice and sea‐surface temperature to run coordinated hindcast experiments with five different atmospheric general circulation models. The multimodel ensemble‐mean results presented in the paper reduce biases of each model and eliminate atmospheric internal unforced variability, and thus provide the best estimate to date of the signal of the polar sea ice loss. The results suggest that the impact of sea ice seems critical for the Arctic surface temperature changes, but the temperature trends elsewhere seem rather due to either sea‐surface temperature changes or atmospheric internal variability. They give clear guidance on how to provide society with more accurate climate change attributions. Our work is of interest to stakeholders of countries in the Northern Hemisphere middle and high latitudes. Key Points: This study shows results from the first coordinated experiments on the sea ice impact for the observed climate change Climate change is coupled with sea ice loss only over the Arctic lower troposphere Models show that sea ice decline was not the cause of the recent colder winters over Siberia